1995
DOI: 10.1039/ft9959102291
|View full text |Cite
|
Sign up to set email alerts
|

Volumetric properties of binary mixtures of water with methoxy(ethoxy)nethanols

Abstract: Density and ultrasonic speed measurements have been made, respectively, by means of a densimeter operating in a flow mode and by a sonic solution monitor using a 'sing-around' technique, for aqueous mixtures of 2-(2-methoxyethoxy)ethanol and 2-[2-methoxy(ethoxy),lethanol, at 298.15 K, across the entire composition range. The density values were readily converted to molar volumes, V, and excess molar volumes, VE. Estimates of the isentropic molar quantity, K,, equal to -(aV/ap), , and of its excess counterpart,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
10
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(12 citation statements)
references
References 26 publications
2
10
0
Order By: Relevance
“…2 ) 2 OH 1016.4 1016.7 (12) 100.4 * 271.1 (12) 1417.1 1415.98 (17) 57.915 1014.45 (17) (18) 115.4 (19) 298.1 (19) 1377.1 1377.22 (19) 73.087 983.589 (19) 984.1 (12) (18) 144.2 (19) 358.4 (19) 1358.3 1357.02 (19) …”
Section: Methodsmentioning
confidence: 97%
“…2 ) 2 OH 1016.4 1016.7 (12) 100.4 * 271.1 (12) 1417.1 1415.98 (17) 57.915 1014.45 (17) (18) 115.4 (19) 298.1 (19) 1377.1 1377.22 (19) 73.087 983.589 (19) 984.1 (12) (18) 144.2 (19) 358.4 (19) 1358.3 1357.02 (19) …”
Section: Methodsmentioning
confidence: 97%
“…Minima of this type are a typical characteristic of amphiphileÈwater systems. 6 The changes with of the partial excess molar volumes for x A water, in the water-rich region of the di †erent mixtures V W E , are plotted in Fig. 3.…”
Section: Resultsmentioning
confidence: 99%
“…It has been shown that the inclusion of one or more oxyethylene groups into an amphiphile molecule increases the LCST and consequently the aqueous miscibility.4,5 The e †ects of enlarging the polar head group by progressive addition of oxyethylene groups into molecules of amphiphiles with di †erent alkylchain lengths were previously explored. 6,7 We thought it worthwhile to measure their magnitude when no alkyl chain is involved in the amphiphile molecule. Consequently, this work explores these e †ects for binary aqueous mixtures of poly (…”
mentioning
confidence: 99%
“…( 27) and (30), and with higher-order partial properties9 in eqn. (31) and (32). A terminology that distinguishes volume-speciÐc quantities6 from quantities speciÐc in the total amount of substance is suggested.…”
Section: Summary Of Conclusionmentioning
confidence: 99%